Electrochemically grafted molecular layers as on-chip energy storage molecular junctions - Kaur, Rajwinder; Malik, Ankur; Gupta, Ritu; Kumari, Kusum; Singh, Saurabh Kumar; Bueno, Paulo Roberto [UNESP]; Mondal, Prakash Chandra (Royal Society of Chemistry (RSC), 2025)
Molecular junctions (MJs) are celebrated nanoelectronic devices for mimicking conventional electronic functions, including rectifiers, sensors, wires, switches, transistors, negative differential resistance, and memory, following an understanding of charge transport mechanisms. However, capacitive nanoscale molecular junctions are rarely seen. The present work describes electrochemically (E-Chem) grown covalently attached molecular thin films of 10, 14.3, and 18.6 nm thickness using benzimidazole (BENZ) diazonium salts on ITO electrodes on a quartz substrate upon which 50 nm of aluminum (Al) top contact was deposited to fabricate large-scale (area = 500 × 500 μm2) molecular junctions. The capacitance of the molecular junctions decreases with increasing thickness of molecular layers, a behavior attributed to a classical dielectric role in which the geometric capacitance of the device within a uniform dielectric component is expected to decrease with increasing thickness. An electrical dipole moment in BENZ oligomers enhances polarizability; hence, the dielectric constant of the medium leads to an increase in the capacitance of MJs, which reaches a maximum value of ∼53 μF cm−2 for a junction of 10 nm molecular film thickness. In addition to direct-current (DC) electrical measurements, and computational studies, we performed alternating current (AC)-based electrical measurements to understand the frequency response of molecular junctions. Our present study demonstrates that BENZ-based molecular junctions behave as classical organic capacitors and could be a suitable building block for nanoscale on-chip energy storage devices.